Phytochemical Screening and Antidiabetic Activity Test of Extracts and Fractions of Lactuca Indica (L.) In Streptozotocin-Induced Diabetic Mice - Rosanto, Tamba; Marline, Nainggolan; Noersal, Rosidah (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The purpose of this study was to determine the antidiabetic effect of ethanol extract and Lactuca indica leaf fraction to determine the effective dose of mice induced with streptozotocin compared with metformin. Design: The design of this study was experimental in which the extraction and fraction of Lactuca indica leaves were tested for the value of decreasing blood glucose levels of mice after induction of streptozotocin. Antidiabetic activity tests were divided into 12 groups. Group I (baseline) group II (negative control) were given CMC 0.5%, Group III (positive control) were given metformin 65 mg/kg BW, while Groups IV to XII were given Lactuca indica leaf extract and fractions at their respective doses -each 100, 150 and 200 mg/kg BW Interventions: The variable that was intervened in this study was the concentration of extract used Main outcome measure: The main measurement results in this study were to determine extracts and fractions that we're able to reduce blood glucose levels in mice. Results: The antidiabetic effect of Lactuca indica leaves shows that EELL, EAFLL and NHFLL have antidiabetic effects, this is supported by the chemical content contained in the extracts, namely flavonoids, tannins, saponins, glycosides and triterpenoids/steroids. The most effective activity to reduce blood glucose levels in streptozotocin-induced mice is EAFLL 100 mg/kg BW Conclusion: ethyl acetate fraction of Lactuca indica leaves has an effective antidiabetic activity at a dose of 200 mg/kg BW has given antidiabetic activity in mice induced by STZ, on the 9th day BGL mice have dropped below 120 mg/dl.